Lacrimal gland removal impairs sexual behavior in mice - Rosa Maria eCavaliere; Filippo eGhirardi; Roberto eTirindelli (Frontiers Media S.A., 2014)
Exocrine gland-secreting peptides (ESPs) are a protein family involved in the pheromonal communication of rodents. ESP1 is a lacrimal peptide synthesized by the extraorbital glands of males of specific mouse strains that modulates the sexual behavior in females. Reportedly, BALB/c males, that produce high level of ESP1 in the tear fluid, were shown to enhance the lordosis behavior in C57BL/6 females during mating. In contrast, C57BL/6 and ICR males, both unable to express ESP1, failed to modulate this sexual behavior. Nonetheless, ICR males did become competent to enhance lordosis behavior in C57BL/6 females providing these were pre-exposed to ESP1. To exclude any strain differences, here, we investigated the pheromonal role of the extraorbital glands and indirectly of ESP1 in animals of the same strain. This was performed by applying the lordosis experimental paradigm in BALB/c mice before and after the surgical removal of these glands in males. The excision of the extraorbital glands reduced but did not abolish the production of ESP1 in the lacrimal fluid of BALB/c mice. An immunological analysis on soluble extracts of the glands that drain into the conjunctival sac revealed that the intraorbital glands are also responsible for the production of ESP1. The removal of both the extra and intraorbital glands completely eliminated the tear secretion of ESP1. Extraorbital gland-deficient BALB/c mice were still able to induce lordosis behavior in sexually receptive females. In contrast, males with the removal of both the extra and intraorbital glands failed to enhance lordosis behavior in females. Unexpectedly, C57BL/6 males did improve this sexual performance in BALB/c females. However, an analysis of the tear fluid of C57BL/6 males revealed low but detectable levels of ESP1. Overall, our study highlights the relevance of the orbital glands in modulating reproductive behavior and the sensitivity of the vomeronasal system to detect trace amount of ESP1.